التطوير التنظيمي للمعاهد الأزهرية الخارجية: رؤية مستقبلية - الهنداوي، أحمد عبد الفتاح حمدي; أحمد، محمود مصطفى أحمد (مجلة التربية : مجلة علمية محكمة للبحوث التربوية و النفسية و الاجتماعية., 2023)
The study aimed to provide a future vision for the organizational development of the external al-Azhar institutes. the study used the forward-looking approach and relied on the Delphi method in its three rounds on a sample of (37) experts closely related to the subject of organizational development in educational institutions, and among the officials of the external al-Azhar institutes in the administrative and technical aspects. in order to determine the requirements for the organizational development of the external al-Azhar institutes, the study reached a proposed vision for the organizational development of the external al-Azhar institutes, which consisted of five dimensions: (the strategic dimension, the human dimension, the technical dimension, the interactive dimension, and the logistical dimension). a well-defined plan and policy for organizational development, including goals, programs and sub-projects, a schedule, implementation practices, follow-up and evaluation, taking into account its coverage of the dimensions of organizational development, in a way that contributes to achieving the strategic vision of al-Azhar pre-university education within a dynamic and changing global framework, and publishing and announcing the activities and efforts of organizational development in al-Azhar external institutes, through various and varied means (digital-non-digital), so that it clarifies what is being accomplished during each of the periods, and what efforts are being made in facing obstacles and challenges, and benefiting from that in setting and developing future plans. هدفت الدراسة إلى تقديم رؤية مستقبلية للتطوير التنظيمي للمعاهد الأزهرية الخارجية، واستخدمت الدراسة المنهج الاستشرافي واعتمدت على أسلوب دلفي بجولاته الثلاثة على عينة بلغت (37) فردا من الخبراء وثيقي الصلة بموضوع التطوير التنظيمي بالمؤسسات التعليمية، ومن مسئولي المعاهد الأزهرية الخارجية في النواحي الإدارية والفنية؛ من أجل تحديد متطلبات التطوير التنظيمي للمعاهد الأزهرية الخارجية، وتوصلت الدراسة إلى رؤية مقترحة للتطوير التنظيمي للمعاهد الأزهرية الخارجية متضمنة خمسة أبعاد هي (البعد الاستراتيجي، البعد البشري، البعد التقني، البعد التفاعلي، البعد اللوجستي)، وأوصت الدراسة بضرورة تبني إدارة المعاهد الأزهرية الخارجية لخطة وسياسة واضحة المعالم للتطوير التنظيمي، متضمنة الأهداف، والبرامج والمشروعات الفرعية، والجدول الزمني وممارسات التنفيذ والمتابعة والتقويم، مع مراعاة تغطيتها لأبعاد التطوير التنظيمي، بما يسهم في تحقيق الرؤية الاستراتيجية للتعليم الأزهري قبل الجامعي في إطار عالمي دينامي متغير، ونشر وإعلان أنشطة وجهود التطوير التنظيمي بالمعاهد الأزهرية الخارجية، عبر وسائل متعددة ومتنوعة (رقمية-غير رقمية)، بحيث توضح ما يتم إنجازه خلال كل فترة من الفترات، وما يبذل من جهد في مواجهة العقبات والتحديات، والاستفادة من ذلك في وضع وتطوير الخطط المستقبلية.